NGOs and the policy‐making process in Russia: The case of child welfare reform. Issue 2 (3rd October 2018) - Bindman, Eleanor; Kulmala, Meri; Bogdanova, Elena
Abstract : This article explores the issue of the major reform of the child welfare sector that has been carried out in Russia in recent years. Focusing on deinstitutionalization and a child's right to a family, this reform moves Russia in the direction of international trends in this area and represents a break with previous state‐ and institution‐dominated approach to "problem families." The article explores how and why this process has come about in a traditionally top‐down hybrid regime and applies the Multiple Streams Framework first developed by Kingdon to argue that Russian child welfare nongovernmental organizations have acted in concert with government officials to act as policy entrepreneurs in framing the policy problem and presenting solutions to it in a way that has influenced national priorities in this area. At the same time, the article acknowledges that major challenges remain in terms of implementing the reform at the regional level of government in Russia.